Selective feeding of the mullet larvae Liza haematocheila during ontogeny in Laizhou Bay, Bohai Sea, China: The importance of small copepods in mesozooplankton as prey - Sun, Xiaohong; Song, Minpeng; Li, Zhengguang; Song, Yan; Yuan, Xiaonan; Dong, Bing; Zhang, Lu; Zhu, Lixin; Liang, Zhenlin (Frontiers in Marine Science, 2023)
The mullet Liza haematocheila is widely distributed in low-salinity waters around the world and has high economic value. However, details regarding the foraging ecology of mullet larvae remain unclear. Larvae of L. haematocheila were sampled in Laizhou Bay of the Bohai Sea, China, in May 2016, and diet composition was detected using gut content analysis to compare differences in feeding parameters and diet shift in dominant prey during ontogeny. The results showed no linear relationship between gape size (GS) and standard length (SL) at larva length <7 mm (flexion larvae, FL), but linear increase was observed for SL >7 mm (post-flexion larvae, PFL). Maximum prey size (MPS) overlapped with GS during the FL stage but was never higher than GS during the PFL stage. Trends of increasing MPS and prey size range (PSR) during the PFL stage were lower than those during the FL stage, but prey number (PN) increased significantly during the PFL stage. Diet composition analyses in mullet larvae showed a total of 10 mesozooplankton species (or categories), of which 8 species were copepods (including copepods nauplii and copepodites), and showed the dominance of 4 small copepods (<1 mm). Analyses of the numerical proportion of dominant copepods showed that the largest prey (Paracalanus parvus) gradually increased as GS increased; conversely, the smallest prey (nauplii of Calanus sinicus) decreased. Collectively, these results suggest that PFL tends to exhibit increased PN but not prey size or size range, and diet shifts from smaller to larger prey during ontogeny in mullet larvae. All these indicate that PFL has higher prey selection ability compared with FL, specifically switching the diet to include larger small copepods during the PFL stage and increasing the prey number instead of increasing prey size. These determine the importance of small copepods in mesozooplankton as dominant prey and facilitate predictions of the impact of climate change on mesozooplankton and fish larvae.